1976
DOI: 10.1039/p29760001337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the oxidation of glyoxylic and pyruvic acids by periodate

Abstract: The kinetics of the oxidation of glyoxylic and pyruvic acids by periodate have been studied at pH 0-9 and 273-303 K. The kinetics are second order, first order in each reactant and the rate has a maximum at pH 6. It is suggested that the dehydrated periodate monoanion lo4is the only reactive periodate species and the or-oxocarboxylic acids and their anions react in their dehydrated forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, it was noted that glycolic acid (CH 2 (OH)CO 2 H) does not practically react with the Mn oxidant that lends support the gem-diol forms of the reducing αoxo acids could be the actual reactive species. Moreover, it is supposed that enolization of pyruvic acid is not apparent here, which becomes prominent when pyruvic acid is used at much higher concentration and at pH higher than 6 [55], conditions far from the present experimental conditions. The absence of oxalic acid in the product solution for pyruvate redox further confirmed the nonreactivity of enol pyruvate in this reaction [56].…”
Section: [Mn 3 (μ-O) 4 (Phen) 4 (H 2 O) 2 ] 4+ + 3rcocoohmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, it was noted that glycolic acid (CH 2 (OH)CO 2 H) does not practically react with the Mn oxidant that lends support the gem-diol forms of the reducing αoxo acids could be the actual reactive species. Moreover, it is supposed that enolization of pyruvic acid is not apparent here, which becomes prominent when pyruvic acid is used at much higher concentration and at pH higher than 6 [55], conditions far from the present experimental conditions. The absence of oxalic acid in the product solution for pyruvate redox further confirmed the nonreactivity of enol pyruvate in this reaction [56].…”
Section: [Mn 3 (μ-O) 4 (Phen) 4 (H 2 O) 2 ] 4+ + 3rcocoohmentioning
confidence: 68%
“…Stepwise one-electron transfer and retention of nuclearity as proposed above are supported by the fact that different oxidation levels of the binuclear catalase enzyme models preserve nuclearity [51], the various oxidation levels (S states) of the manganese cluster in PSII also apparently retain bond connectivity [2] and high valent manganese has a propensity to form (μ-oxo) complexes in weakly acidic media [52]. The oxidation rates of glyoxylic and pyruvic acids by periodate were increased on increasing pH, and the authors suggested the reactions proceed through the nucleophilic attack of periodate to the carbonyl group of the α-oxo acids where the hydrated forms were nonreactive [55]. However, a reverse trend was found in this study-an increase in the rate with decreasing pH that might be due to weaker reactivity of the reducing anions in comparison to their parent acids.…”
Section: [Mn 3 (μ-O) 4 (Phen) 4 (H 2 O) 2 ] 4+ + 3rcocoohmentioning
confidence: 99%
“…We, in this report, describe the kinetics * Author for correspondence and mechanism of pyruvate oxidation by the silver(III) complex under reference. We found kinetic evidence that the title complex oxidises glyoxylic acid by a two step one-electron transfer process [5], and thus we thought it worthwhile to oxidise pyruvic acid by the silver(III) complex to substantiate (or, compare) the mechanistic aspects of electron transfer as glyoxylic acid and pyruvic acid are in many ways kinetically comparable in their oxidations [15][16][17].…”
Section: Introductionmentioning
confidence: 95%
“…Mechanistic studies on pyruvate oxidation by highervalent metals are not very common [15][16][17][18][19]. Silver(III) in the title complex is much stabilised by the acyclic tetraaza ligand and is inert to substitution (d 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…P.; Bannister, C. E.; Margerum, D. W., to be submitted for publication. (12) Pagenkopf, G. K.; Margerum, D. W. J. Am.…”
mentioning
confidence: 99%